Watchful Waiting for Cases of Pediatric Otitis Media: Modeling Parental Response to Physician Advice. Issue 8 (2nd August 2016) - MacGeorge, Erina L.; Smith, Rachel A.; Caldes, Emily P.; Hackman, Nicole M.
Abstract : Watchful waiting (WW) can reduce unnecessary antibiotic use in the treatment of pediatric otitis media (ear infection), but its utility is impaired by underutilization and noncompliance. Guided by advice response theory, the current study proposes advantage and capacity as factors that predict how caregivers evaluate and respond affectively to WW. Parents ( N = 373) of at least 1 child age 5 years or younger completed questionnaires that assessed responses to hypothetical WW advice for their youngest child. Perceptions of advantage from WW and the capacity to monitor and manage symptoms predicted advice quality, physician trust, and future compliance both directly and indirectly through negative affect. The findings suggest the elaboration of advice response theory to include more aspects of advice content evaluation (e.g., advantage) and the influence of negative affect. The study also provides practical guidance for physicians seeking to improve caregiver reception of WW advice.